2018
DOI: 10.1159/000495556
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin-β4 Mediates Hepatic Stellate Cell Activation by Interfering with CircRNA-0067835/miR-155/FoxO3 Signaling Pathway

Abstract: Background/Aims: Hepatic stellate cells (HSCs) are the primary cell type responsible for liver fibrosis. Our study proved that thymosin beta 4 (Tβ4) has anti-fibrogenic effects in HSCs through PI3K/AKT pathway. However, the underlying mechanisms are not fully elucidated. Circular RNAs (circRNAs) play important roles in fine-tuning gene expression and are often deregulated in cancers. However, the expression profile and clinical significance of in liver fibrosis is still unknown. Therefore, we hypothesize that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 17 publications
0
41
0
Order By: Relevance
“…Among these circRNAs, circRNA_34116 was shown to inhibit HSCs activation possibly via miR-22-3p and its targets, BMP7 as predicted by the bioinformatics analysis (Zhou Y. et al, 2018). Another study of HSC inhibition by thymosin beta 4 treatment has identified 644 circRNAs that were differentially expressed and circRNA_0067835 expression was significantly increased in activated HSCs (Zhu L. et al, 2018). It was also shown that circRNA_0067835 acted as a miR-155 sponge and elevated the FOXO3a expression thus promoted HSCs activation and fibrosis (Zhu L. et al, 2018).…”
Section: Non-coding Rnas In Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these circRNAs, circRNA_34116 was shown to inhibit HSCs activation possibly via miR-22-3p and its targets, BMP7 as predicted by the bioinformatics analysis (Zhou Y. et al, 2018). Another study of HSC inhibition by thymosin beta 4 treatment has identified 644 circRNAs that were differentially expressed and circRNA_0067835 expression was significantly increased in activated HSCs (Zhu L. et al, 2018). It was also shown that circRNA_0067835 acted as a miR-155 sponge and elevated the FOXO3a expression thus promoted HSCs activation and fibrosis (Zhu L. et al, 2018).…”
Section: Non-coding Rnas In Nafldmentioning
confidence: 99%
“…Another study of HSC inhibition by thymosin beta 4 treatment has identified 644 circRNAs that were differentially expressed and circRNA_0067835 expression was significantly increased in activated HSCs (Zhu L. et al, 2018). It was also shown that circRNA_0067835 acted as a miR-155 sponge and elevated the FOXO3a expression thus promoted HSCs activation and fibrosis (Zhu L. et al, 2018). Despite these limited findings of circRNAs roles in liver fibrosis, the evidence of their regulatory interaction with miRNAs and their target mRNAs showed that understanding the molecular regulation and mechanisms underlying liver fibrosis could potentially discover a novel therapeutic target.…”
Section: Non-coding Rnas In Nafldmentioning
confidence: 99%
“…miR-155 is upregulated in a NASH mouse model induced via high fat diet [98]. iR-155 elevates the Forkhead-Box-Protein O3 (FOXO3a) expression thereby regulating the activation of that pathway, whose proteins are involved in the maintenance of the intercellular redox balance [99]. Additionally, miR-155 regulates lipid metabolism by modulating the protein expression of SREBP-1c and fatty acid synthase (FAS) resulting in increased intracellular lipid accumulation in hepatocytes [100].…”
Section: Nonalcoholic Fatty Liver Disease (Nafld) and Nonalcoholicmentioning
confidence: 99%
“…LX2 cells were transfected with RAC1 siRNA with or without miR-146a-5p inhibitor and then subjected to 8 Gy X-ray irradiation. (Zhu et al, 2018). It was reported that microRNA-146b regulates HSC activation via targeting of KLF4 (Ge et al, 2016).…”
Section: Discussionmentioning
confidence: 99%